Regimes of meaning and forms of mediation in post-digital marketing strategies - Ciaco, João Batista (Revista Acta Semiotica, 2021)
This article seeks to understand the paradoxical condition of the contemporary “post-consumption” based on the interactions that are interwoven between consumers, brands and companies, as well as to describe the marketing strategies that brands elaborate to better meet their business purposes. Between hyper-consumerism as a source of (supposed) full satisfaction of desires and its denial as a way of confronting the established system, these so-called “post-consumers” seem to establish an immediate relationship between the very meaning of their lives and the act of consuming. As a consequence, to build efficient branding and business strategies, post-digital marketing has to reorganize itself, mainly by transforming the regime of its interactions (as defined by the sociosemiotics narrative grammar) with this paradoxical subject of consumption.